Myth in Pride and Prejudice - Saputri, Nia Liska; Ramadhianti, Agustina; Hadi, Irfan (IJOSMAS, 2024)
By using Roland Barthes' myth theory as a lens, this research attempts to understand Mrs. Bennet's role in Jane Austen's Pride and Prejudice. The story of social norms and women's standing in the early 19th century is greatly influenced by Mrs. Bennet, who is frequently seen as an example of an obnoxious and foolish housewife. The present research applies Barthes' myth theory to investigate how Mrs. Bennet's persona both reflects and perpetuates prevailing cultural beliefs regarding women's roles, marriage, and social stratification in Elizabethan English society. This study employs a qualitative descriptive method. This research result is finding out that the hidden meaning or myth in this film that Mrs. Bennet is not simply a humorous figure, but also a symbol of the social pressures that middle-class mothers experience in marrying off their children in order to increase their social standing and economic security. The present research uses semiotic analysis to show how Mrs. Bennet's behaviour and concern with marriage can be interpreted as a manifestation of a myth that relates a woman's worth to her marriage success, hence perpetuating gender stereotypes and divides between classes.